Numerical simulation of passive-suction-jet control of flow over two side-by-side circular cylinders. (1st August 2022) - Chen, Wen-Li; Min, Xiang-Wei; Guo, Yan-Jiao
Abstract: A passive-suction-jet control scheme was adopted to manipulate the periodic vortex shedding of two side-by-side circular cylinders. The baseline case (both cylinders without control), Case #1 (only the lower cylinder was controlled), and Case #2 (both cylinders were controlled) were numerically simulated at five spacing ratios ( S R ) of 1.5, 2.0, 2.5, 3.0, and 4.0. The results show that the cylinders in all three cases experience a biased flow pattern at S R  = 1.5 and 2.0 and tend to behave as isolated cylinders at S R  > 2.0. The flow structures in Case #2 reveal that at S R  = 1.5 and 2.0, the jets blown from the pipes roll up to form a large-scale vortex behind one cylinder and a series of small-scale vortices behind the other, eliminating the periodic vortex shedding of the two cylinders completely and yielding low fluctuating lifts. At S R  > 2.0, the vortices formed by the jets weaken the influence of the wake vortices on the cylinders, contributing to a 94% reduction in lift fluctuation on average. Moreover, the holes centered at θ  = 75°–135° were revealed to play an important role in continuously pouring positive vorticities into the fluid, which manipulate the periodic vortex shedding. Highlights: The control effectiveness of passive-suction-jet pipes on the flow over two side-by-side cylinders was examined. The jets eliminated the periodic vortex shedding when both cylinders were controlled at spacing ratios of 1.5 and 2.0. The lift fluctuation was reduced by 94% on average when both cylinders were controlled at spacing ratios lager than 2.0. The boundary vorticity flux distribution reveals the control mechanism of the pipes.